Speak So I May See You: Doing Public Theology in an Arab-Muslim Context - Estafanos, Eshak (International journal of public theology, 2024)
Public theology is a contemporary field that transcends mere trendiness; it stands as a vital imperative for the Arab Church. This imperative arises not only from the need for effective communication with its counterparts but also as a means to bridge the cultural chasm between the East and the West. Rooted in historical legacies and lived realities, Arab Christian theology boasts rich wellsprings of wisdom, yet it also confronts distinct challenges. While it shares commonalities with global public theology, the Arab Church’s presence in this pivotal region renders its public theology distinctive and profoundly significant.